Issues of Public Administration in the Age of Digitalization - O. A. Mazaev (Теоретическая и прикладная юриспруденция)
The subject of the study is the possibility of citizens’ participation in public administration through the use of modern information technologies (hereinafter — IT). The article analyzes in detail the issues of public attitudes towards the use of IT. It is shown how in the conditions of increasing influence of actively developing IT, which plays a central role in the formation of modern economy and has a significant impact on various aspects of economic growth, productivity and innovation, despite the lack of a universally recognized definition of the category “public administration”, the readiness of people to use IT to participate in public administration is clearly seen, while at the same time the legislators perceive it as some private novelties, but not as a system-forming force, capable of using IT in public administration. The methodological basis of the work was the general scientific methods of system analysis and generalization of normative, scientific and practical materials and others. The scientific novelty of the article is determined by the fact that it is a comprehensive study of the possibility of citizens to use information technologies and systems in public administration. The most significant results include the formulated proposals to improve the current legislation, as well as the existing law enforcement practice.